2006
DOI: 10.1016/j.febslet.2006.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Intron exclusion and the mystery of intron loss

Abstract: Mechanisms for loss and gain of introns are elusive. Reported here is a new pattern of intron loss which features a random loss of a single intron in a multiple-intron gene with its neighboring introns remained, which process is defined as intron exclusion. Intron exclusion is reminiscent of removal of a limited stretch of non-homologous sequence in a homologous recombination (HR) triggered by a double strand break (DSB), and therefore lends further evidence for a theory of intron loss through HR between a cDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…An increased rate of intron loss might thus be facilitated by the extraordinarily high rate of DNA repair by homologous recombination in P. patens . This hypothesis is based on models proposing a prominent role of gene conversion and DNA repair in intron loss [84,85]. …”
Section: Resultsmentioning
confidence: 99%
“…An increased rate of intron loss might thus be facilitated by the extraordinarily high rate of DNA repair by homologous recombination in P. patens . This hypothesis is based on models proposing a prominent role of gene conversion and DNA repair in intron loss [84,85]. …”
Section: Resultsmentioning
confidence: 99%
“…4). Intron length variation probably is an outcome of recombination46. Variable introns would increase genome diversity by permitting different recombination arrangements and would accelerate the proteome evolution by differential splicing4748, which could benefit organism fitness and contribute not only to gene family divergence but also to species diversity and differentiation47.…”
Section: Resultsmentioning
confidence: 99%
“…Because these losses were adjacent and appear to have occurred simultaneously, we assume these introns were deleted by RTMIL. The exact mechanism by which RTMIL may remove internal or 5' intron(s) but conserve 3' intron(s) has proved elusive but received considerable attention [9,11,13,44,51,52]. The most commonly proposed mechanism to account for internal or 5' intron loss(es) by RTMIL is the formation of a double stranded mRNA secondary structure upstream from the 3' conserved intron position(s).…”
Section: Resultsmentioning
confidence: 99%
“…By identifying orthologs, aligning gene sequences, and coupling intron absences/presences with known species phylogenies, numerous studies have identified the number of intron gains and losses that have occurred among species throughout evolution [1-11]. However, very little is known about the molecular mechanisms underlying these changes [12,13]. …”
Section: Introductionmentioning
confidence: 99%